Nonstationary temperature distribution over the depth of a plate with an elongated defect in inspection by constant and impulse thermal flow; The Soviet journal of nondestructive testing; Vol. 13, iss. 2 - Vavilov V. P. Vladimir Platonovich (1977, 1977)
An algorithm is described for numerically calculating the temperature field in inspecting with a thermal flow arbitrarily changing with time, in particular by constant and impulse ones, taking into consideration the final thickness and thermophysical properties of the defect. As a concrete example, the temperature distribution over the depth of parts in the area of a defect is shown.